Theory and Application of Agricultural Energy Internet Considering Coupling of Agriculture, Meteorology and Energy - Lingxi MA; Xueqian FU (Zhongguo dianli)
Under the background of vigorously developing energy internet and building facility agriculture in China, meteorology is an important factor affecting the seasonality of agricultural power load side and the uncertainty of agricultural new energy power generation side. In order to provide new ideas for the mutual promotion of new energy development and agricultural development, it is necessary to study the agricultural energy internet (AEI) of agriculture-meteorology-energy coupling. Based on an investigation of the research status of energy meteorology, agrometeorology and agricultural energy internet, the coupling mechanism of agriculture, energy and meteorology is summarized. The impact of their coupling is studied. The application scenarios of important technologies for dealing with the impact of energy meteorology and agrometeorology are elaborated under the framework of agricultural energy internet system. And the agricultural energy internet of agriculture-meteorology-energy coupling is analyzed from three levels. The results of this paper can provide a reference for the future research of agricultural energy internet.